2018
DOI: 10.1111/jgs.15675
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Stewardship Programs in Long‐Term Care Settings: A Meta‐Analysis and Systematic Review

Abstract: BACKGROUND Antimicrobial stewardship programs have been established in hospitals, but less studied in long‐term care facilities (LTCFs), a setting with unique challenges related to patient populations and available resources. This systematic review sought to provide a comprehensive assessment of antimicrobial stewardship interventions implemented in LTCFs, using meta‐analysis to examine their impact on overall antimicrobial use. METHODS Electronic searches of MEDLINE, Embase, and CINAHL (1990 to July 2018) ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 40 publications
6
52
0
Order By: Relevance
“…Findings from a meta-analysis and systematic review of ASPs in nursing homes 40 are consistent with our results. They highlight some critical necessities of successful ASP implementation, particularly the importance of behavior change.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Findings from a meta-analysis and systematic review of ASPs in nursing homes 40 are consistent with our results. They highlight some critical necessities of successful ASP implementation, particularly the importance of behavior change.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with literature describing the ineffectiveness of solely educational interventions. 40 Participants consequently considered the need for multifaceted interventions, or bundling several interventions together, to provide meaningful prescribing changes. Multifaceted interventions were included in the first round of the survey, and although the intervention received favorable scores, the intervention was eliminated from the second round of the survey due to consensus regarding its lack of feasibility in nursing homes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54,56,57 Differences in the implementation rates of ASP policies might reflect variations in resource intensiveness, or NHs may have begun incrementally building their ASPs starting with policies for which resources were more readily accessible such as tracking antibiotics use. 58 Rates of NHs that gave feedback on prescriptions to providers was very different between comprehensive ASPs and not comprehensive ASPs, and a systematic review has found that this practice can increase the effects of antibiotic stewardship interventions. 59 Additionally, comparatively few NHs with not comprehensive ASPs provided educational materials on improving antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…The present study aimed to build upon and update the existing systematic reviews of antimicrobial stewardship programmes in LTCFs [32][33][34][35][36] by applying these behavioural science frameworks to specify the components of existing interventions in this context, as a basis for identifying those that are associated with improved outcomes. The specific research questions were:…”
Section: Introductionmentioning
confidence: 99%